Perceiving outcomes as determined by external forces: The role of event construal in attenuating the outcome bias - Savani, Krishna (2017)
People view the same decision as better when it is followed by a positive outcome than by a negative outcome, a phenomenon called the outcome bias. Based on the idea that a key cause of the outcome bias is people’s failure to appreciate that outcomes are in part determined by external forces, three studies tested a novel method to reduce the outcome bias. Experiment 1 showed that people who construed a person’s interactions with the environment as events rather than as actions or choices were less susceptible to the outcome bias in a medical decision making task. Experiments 2 and 3 demonstrated that people who recalled past events rather than actions or choices exhibited lower outcome bias in a risky decision making task and in an ethical judgment task. These findings indicate that an event construal helps people appreciate the role of external factors in causing outcomes.